Tropomyosins in mosquito and house dust mite cross‐react at the humoral and cellular level. Issue 10 (14th August 2018) - Cantillo, Jose F.; Puerta, Leonardo; Fernandez‐Caldas, Enrique; Subiza, Jose L.; Soria, Irene; Wöhrl, Stefan; Ebner, Christof; Keller, Walter; Resch‐Marat, Yvonne; Vrtala, Susanne; Bohle, Barbara
Summary: Background: Aedes aegypti and Dermatophagoides pteronyssinus contain important allergens including cross‐reactive tropomyosins. However, the functional and clinical relevance of their cross‐reactivity is still debated. Objective: To analyse the humoral and cellular cross‐reactivity of recombinant Aed a 10.01, Aed a 10.02 and Der p 10. Methods: Sera from 15 Austrian house dust mite‐allergic, Der p 10‐sensitized individuals were tested for IgE reactivity to recombinant tropomyosins in ELISA, inhibition ELISA and basophil activation tests. BALB/c mice were immunized with Aed a 10.01 or Aed a 10.02, and their sera were assessed for reactivity to all tropomyosins. Splenocytes were stimulated with all tropomyosins and synthetic peptides representing the amino acid sequence of Aed a 10.01. Results: IgE antibodies of Der p 10‐sensitized patients cross‐reacted with both tropomyosins from A. aegypti . Aed a 10.01 was a more potent inhibitor of IgE binding to Der p 10 and a stronger activator of basophils sensitized with Der p 10‐specific IgE than Aed a 10.02. Murine antibodies raised against Aed a 10.01 and Aed a 10.02 cross‐reacted with Der p 10. Aed a 10.01‐specific antibody showed stronger cross‐reactivity with Der p 10 than Aed a 10.02‐specific antibody. Splenocytes from both groups of mice proliferated similarly to all tropomyosins. Five cross‐reactive T cell‐activating regions were identified. Conclusion and Clinical relevance: Tropomyosins from D. pteronyssinus and A. aegypti show humoral and cellular cross‐reactivity, involving 5 potential T cell‐activating regions. The more pronounced cross‐reactivity of Aed a 10.01 and Der p 10 matched the higher sequence similarity of both proteins.